2016
DOI: 10.1002/cppb.20037
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Imaging of Metabolites in Barley Grain Tissues

Abstract: Higher plants are composed of a multitude of tissues with particular functions, reflected by distinct profiles of transcripts, proteins, and metabolites. Although the rapid development of "omics" technologies has advanced plant science tremendously within recent years, analysis is frequently performed on whole organ or whole plant extracts, causing the loss of spatial information. Mass spectrometry-based imaging (MSI) approaches have become a powerful tool to decipher spatially resolved molecular information. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Sectioning of barley grains and matrix application was performed following Peukert et al (2014). The MS imaging (MSI) measurements were performed using an ultrafleXtreme matrix-assisted laser desorption/ionization (MALDI) time-of-flight (TOF)/TOF device (Bruker Daltonics) following Peukert et al (2016a).…”
Section: Methodsmentioning
confidence: 99%
“…Sectioning of barley grains and matrix application was performed following Peukert et al (2014). The MS imaging (MSI) measurements were performed using an ultrafleXtreme matrix-assisted laser desorption/ionization (MALDI) time-of-flight (TOF)/TOF device (Bruker Daltonics) following Peukert et al (2016a).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it is essential to quantify and identify changes in metabolite composition through proper analytical methods. Nowadays, various integrated technologies are used, such as nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry (MS), capillary electrophoresis-MS (CE-MS), liquid chromatography-MS (LC-MS), gas chromatography-MS (GC-MS), and Fourier transform ion cyclotron resonance-MS (FT-ICR-MS) Vinaixa et al 2016;Peukert et al 2016;Mitchell et al 2018). With the advancement of MS-imaging techniques, including matrix-assisted laser desorption (MALDI) and desorption electrospray (DESI) ionization platforms combined with high-resolution MS, it is feasible to conduct in-situ metabolome analysis (Blanksby and Mitchell 2010).…”
Section: Low Molecular Weight Metabolitesmentioning
confidence: 99%
“…In addition, the type and number of constituent sugars, and the mode of binding between them adds to the diversity of carbohydrates. The distribution of carbohydrates in foods such as strawberries [42,69], barley grain [55], maize seeds [66], and apples [47,82] were analyzed by DESI and MALDI-MSI (Table 3). Horikawa et al confirmed the distribution of hexose, sucrose, and sorbitol in apples by MALDI-MSI; there was a linear correlation between the results of HPLC analysis and the ion intensity obtained by MSI, which demonstrated that MSI can quantify simple sugars in tissue sections [82].…”
Section: Carbohydratesmentioning
confidence: 99%